The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1149/2162-8777/ac17bc
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Morphology and Surface Modification of MgO on Thermal Characteristics of Epoxy Composite

Abstract: The advancement in electronic device miniaturization has led to an increase in thermal issues. The reliability of these devices depends on heat dissipation, leading to the development of thermal interface materials (TIMs). In this study, the influence of morphology and surface modification on the thermal characteristics of magnesium oxide (MgO) incorporated epoxy composites was investigated. A wet precipitation method was employed for the synthesis of spherical S-MgO. However, oblong hexagonal H-MgO was obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Therefore, to enhance the bonding strength between PDMS an the hydrophilic surface of the MgO structures was modified to a hydrophobic using APTES, which is a silane coupling agent. This modification prevented the ysis of MgO and suppressed the formation of pores at the interface between th and polymer matrices [28]. A thin layer was uniformly coated on the surface modified MgO structures without a significant collapse in the structure (Figur Figure 3c illustrates the FT-IR spectra of the unmodified MgO and APTES and m MgO structures.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, to enhance the bonding strength between PDMS an the hydrophilic surface of the MgO structures was modified to a hydrophobic using APTES, which is a silane coupling agent. This modification prevented the ysis of MgO and suppressed the formation of pores at the interface between th and polymer matrices [28]. A thin layer was uniformly coated on the surface modified MgO structures without a significant collapse in the structure (Figur Figure 3c illustrates the FT-IR spectra of the unmodified MgO and APTES and m MgO structures.…”
Section: Resultsmentioning
confidence: 99%
“…They have reported that the MgO filler content was ≈20 wt.% which was much lower than 90 wt.% of a commercial alumina TIM. [ 14 ] Hence, MgO and the other materials [carbon nano‐tube (CNT), BN etc.] are used together to obtain the high thermal conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the TIM studies have begun to utilize MgO as a thermal filler material, TIM which has a low ratio of MgO filler ratio (≈20 wt.%) has been reported continuously. [ 14 ] In order to obtain high thermal conductivities in heat dissipation materials, the ratio of thermal filler must be high, and the ratio of ceramic filler is ≈90 wt.% in commercial heat dissipation materials. The usage of MgO alone as a ceramic filler is difficult, since MgO does not mix well with polymers due to the rough surface of a MgO filler.…”
Section: Introductionmentioning
confidence: 99%
“…6d). 2,5,7,9,11,[35][36][37][38][39][40][41][42][43][44][45][46]48 The heat transfer pathway of foams largely depends on their composition. Herein, MgO/Mg(OH) 2 /C foams are composed of MgO, Mg(OH) 2 , and amorphous C; MgO/Co/C foams consist of Co 0 , MgO, and amorphous C. Heat is transferred via electrons in Co 0 and crystal lattice vibrations (phonons) in MgO, Mg(OH) 2 , amorphous C, and pure silica films.…”
Section: The Thermal Performance and Mechanism Of Mgo/co/c Foamsmentioning
confidence: 99%